2021
DOI: 10.1007/s10926-021-09998-z
|View full text |Cite
|
Sign up to set email alerts
|

In What Ways Does Health Related Stigma Affect Sustainable Employment and Well-Being at Work? A Systematic Review

Abstract: Purpose Studies are increasingly showing that health related stigma is a barrier to employment, but it is not known how. The aim of this systematic review is to identify, appraise and analyse studies that have directly or indirectly addressed ways in which stigma affects sustainable employment and well-being at work of people with disabilities. Methods Using a multiphase screening process, this review is based on a comprehensive literature search (2000–201… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
21
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 40 publications
(40 citation statements)
references
References 113 publications
(280 reference statements)
1
21
0
Order By: Relevance
“…People with disabilities who do not disclose may be deprived of accommodations that ensure job tenure [ 38 ]. Moreover, anticipated stigma and perceived discrimination were reported to discourage people with disabilities from pursuing employment or maintaining it [ 39 ]. It is also reasonable to imagine that stigma and discrimination may explain decisions of employment termination taken by the employer “based” on fictitious or misleading arguments.…”
Section: Discussionmentioning
confidence: 99%
“…People with disabilities who do not disclose may be deprived of accommodations that ensure job tenure [ 38 ]. Moreover, anticipated stigma and perceived discrimination were reported to discourage people with disabilities from pursuing employment or maintaining it [ 39 ]. It is also reasonable to imagine that stigma and discrimination may explain decisions of employment termination taken by the employer “based” on fictitious or misleading arguments.…”
Section: Discussionmentioning
confidence: 99%
“…Also other studies that were not particularly related to the workplace showed that disclosure can lead to acceptance and support [5], and, after completing the Coming Out Proud program, decreased self-stigma and diminished depression [6]. Nevertheless, disclosure can also be a barrier as it can lead to adverse employment outcomes due to stigma and discrimination, such as problems obtaining a job [1,[7][8][9][10], job loss [8,11], limited advancement opportunities [8,12], and harassment at work [13,14]. Also outside the workplace mental illness disclosure can lead to increased self-stigma, shame, harm and discrimination [5].…”
Section: Introductionmentioning
confidence: 99%
“…Employees in our study generally spoke positively about the attitude of supervisors. It is important that supervisors maintain this attitude because research showed that negative attitudes from the supervisor to employees has a negative influence on sustainable employability [28]. However, employees that we interviewed indicated that the attitude of their supervisor was not always good.…”
Section: Working Conditions and Working Relationsmentioning
confidence: 88%